Media use and organ donation willingness: A latent profile analysis from Chinese residents - Fangmin Gong; Yuhan Jia; Jinzi Zhang; Meiling Cao; Xiaocen Jia; Xinying Sun; Yibo Wu (Frontiers Media S.A., 2022)
BackgroundPrevious studies have paid attention to media as an important channel for understanding organ donation knowledge and have not divided groups according to the degree of media use to study their differences in organ donation. Therefore, the purpose of this study is to explore the influence of media use on organ donation willingness and the influencing factors of organ donation willingness of people with different media use levels.MethodsA cross-sectional study of residents from 120 cities in China was conducted by questionnaire survey. Using Mplus 8.3 software, the latent profile analysis of seven media usage related items was made, and multiple linear regression was performed to analyze the influence of varying levels of media use on organ donation willingness of different population.ResultsAll the interviewees were divided into three groups, namely, "Occluded media use" (9.7%), "Ordinary media use" (67.1%) and "High-frequency media use" (23.2%). Compared with ordinary media use, high-frequency media population (β = 0.06, P < 0.001) were positively correlated with their willingness to accept organ donation, residents who used media occlusion (β = −0.02, P < 0.001) were negatively correlated with their willingness to accept organ donation. The influencing factors of residents' accept willingness to organ donation were different among the types of occluded media use, ordinary media use and high-frequency media use.ConclusionIt is necessary to formulate personalized and targeted dissemination strategies of organ donation health information for different media users.